Uranium and nuclear power: The role of exploration information in framing public policy - Charles F. Mason (Fondazione Eni Enrico Mattei (FEEM), 2013)
As addressing climate change becomes a high priority it seems likely that there will be a surge in interest in deploying nuclear power. Other fuel bases are too dirty (coal), too expensive (oil, natural gas) or too speculative (solar, wind) to completely supply the energy needs of the global economy. To the extent that the global society does in fact choose to expand nuclear power there will be a need for additional production. That increase in demand for nuclear power will inevitably lead to an increase in demand for uranium. While some of the increased demand for uranium will be satisfied by expanding production from existing deposits, there will undoubtedly be pressure to find and develop new deposits, perhaps quite rapidly. Looking forward, it is important that policies be put in place that encourage an optimal allocation of future resources towards exploration. In particular, I argue there is a valid concern that privately optimal levels of industrial activity will fail to fully capture all potential social gains; these sub-optimal exploration levels are linked to a departure between the private and social values of exploration information.
Keywords: Q48; L72; D83; 330; uranium; nuclear power; exploration